Suicide prevention curriculum development for health and social care students: Protocol for a scoping review. - Kerrie Gallagher; Clíodhna O' Brien; Michelle O' Driscoll; Doireann Ní Dhálaigh; Paul Corcoran; Eve Griffin (PLoS ONE)
Suicide has become a serious public health concern and international research has shown that the majority of individuals who die by suicide had receive healthcare in the year prior to their death. This presents an opportunity for suicide prevention by strategically training healthcare students in suicide prevention knowledge and skills. The objective of this scoping review is to identify literature that describes the design, development, implementation and/or evaluation of suicide prevention training for healthcare and/or social care students in higher education settings. Studies will only be considered eligible for inclusion if they describe the design, development, implementation and/or evaluation of suicide prevention curricula being delivered to healthcare or social care degree students in higher education. Quantitative, qualitative, and mixed method studies published between 2011 and 2023 (inclusive) and in the English language will be considered eligible. This scoping review will be conducted according to the PRISMA guidelines for scoping reviews (PRISMA-ScR). The developed search strategy will be implemented across six databases: PubMed, ERIC (Education Resources Information Center), PsycINFO, Embase, CINAHL and Web of Science. Several grey literature sources will also be consulted. Further potential results will be located by hand-searching the reference lists of included articles. The search strategy will include variations of the terms: 'student', 'suicide prevention' and 'education'. The search will be limited to titles, abstracts, and keywords in databases that allow it. Two reviewers will complete the screening using the predefined inclusion criteria. A third reviewer will resolve any conflicts during the screening and eligibility appraisal processes. Results will be presented in the form of tabulated results and an accompanying narrative summary, describing key findings and context related to learning outcomes, methodologies employed and implementation of the identified programmes.